Ewing Sarcoma in the Fifth Metacarpal of an Adult Woman: A Case Report. Issue 4 (October 2016) - Mahan, M. Chad; Frisch, Nicholas; Durrant, Broc; Parsons, Theodore; Woods, Tammy; Mott, Michael
Abstract : Case: Atypical presentations of Ewing sarcoma (ES) can lead to misdiagnosis and delays in treatment. We present a rare case of ES in the hand of an adult woman who underwent multiple interventions prior to referral to our institution. At 22 months after definitive treatment, the patient remained pleased with the result and had no evidence of recurrence. Conclusion: To our knowledge, ES of the hand in an adult woman has not yet been reported in the literature, and a lack of recognition of this condition might be secondary to the absence of features traditionally associated with malignant bone neoplasms. A broader differential diagnosis after intervention failures offers the opportunity for diagnosis and appropriate treatment.